ANALISIS BERNALAR KRITIS DALAM BUKU AJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS IX SMP KURIKULUM MERDEKA BELAJAR - Tajriyah Tajriyah; Fadlilatul Ashri, Rezza Miftachu Rizqi, Muhammad Naufal Abdad, Abdul Fadhil (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the integration of critical reasoning skills in the Islamic Religious Education and Ethics class IX textbook published by the Ministry of Education and Culture based on the Independent Learning Curriculum. A descriptive qualitative approach is used to evaluate the content of textbooks through critical thinking indicators developed by Robert Ennis, including basic clarification, basic support, inference, advanced clarification, and strategies and tactics. The results of the study show that the textbook as a whole has integrated various activities that support the development of students' critical thinking skills, such as analyzing arguments, assessing the credibility of sources, drawing conclusions, defining terms, and designing problem-solving strategies. This research provides recommendations for teachers to choose appropriate teaching materials and design learning that is able to encourage the development of students' critical thinking skills optimally.